Ending Null Pointer Crashes. - Meyer, Bertrand (Communications of the ACM, 2017)
The article discusses the role that what are referred to as null (also known as nil, or void) pointers play in the developing of computer bugs, or viruses, including in regard to virus prevention and null pointer dereferencing in Common Vulnerabilities and Exposures Database (CVE). An overview of the computer programming language Eiffel, including its role in preventing viruses in computer codes, is provided.